Earthquake Disaster Preparedness Among Teachers in The Special School - Ade Surya Dwiyanti; Etika Emaliyawati; Ristina Mirwanti (Universitas Padjadjaran, 2022)
The level of teachers' disaster preparedness in schools is one thing that influences the impact of disasters on children with disabilities, especially earthquakes, which can occur at any time, including during school hours. Therefore, this study aims to determine the description of earthquake disaster preparedness for special school teachers. This study used a quantitative descriptive method with a total sample of 37 teachers at Cileunyi State SLB, and the total sampling technique used was this study. Preparedness measurement for SLB teachers uses instruments modified according to research needs. Data analysis with frequency distribution and results were grouped into ready and unprepared categories. The results showed that 86.5% of teachers were categorized as 'ready'. The best preparedness parameter is disaster knowledge, while the lowest is disaster warning. From the study results, it can be concluded that most SLB teachers are categorized as ready to face earthquake disasters. However, it is expected that efforts to improve aspects of disaster warning can be carried out, such as providing disaster warning tools, especially for children with disabilities.